TINGKAT AKSESIBILITAS PEJALAN KAKI (STUDI KASUS PEJALAN KAKI STASIUN DEPOK BARU) - Hobir Nur Ikhsan; Winoto Hadi; Yusfita Chrisnawati (Teknik Sipil, Fakultas Teknik Universitas Negeri Jakarta, 2019)
This research aims to find out the accessibility levels for pedestrian in Depok Baru Stastion based on time. The method used is observation include with the desk approach. The research is to find out walking distance the pedestrian walking along transfer process for transportation mode. Number of pedestrians that will be taken as many as 100 pedestrians from 3 points. The result of this research will accessibility index (AI) score with Public Transportation Accessibility Levels (PTAL) which based on time and transportation mode (railway as commuter line and car public transport). The result showed accessibility index levels for commuter line at 06.00 – 09.00 is 8,36 (poor) from Raya Margonda, and 9,37 (poor) from market area and Jl. Baru. Accessibility indeks levels for commuter line at 09.00 – 12.00 is 8,35 (poor) from Jl. Raya Margonda, 5,14 from Jl. Baru, and 5,00 from market area (very poor). Accessibility indeks levels for car public transport at 12.00 – 15.00 is 36,45 (excellent) to Jl. Raya Margonda, 36,46 (excellent) to Jl. Baru, and 84,29 (excellent) to market area. Accessibility index levels for car public transport at 15.00 – 18.00 is 27,35 (excellent) to Jl. Raya Margonda, 45,36 (excellent) to Jl. Baru, and 36,72 (excellent) to market area. Overall, accessibility index levels at Depok Baru Station is poor for commuter line and excellent for car public transport.